Health Consequence Scales for Use in Health Impact Assessments of Climate Change - Brown, Helen (MDPI, 2014)
While health impact assessment (HIA) has typically been applied to projects, plans or policies, it has significant potential with regard to strategic considerations of major health issues facing society such as climate change. Given the complexity of climate change, assessing health impacts presents new challenges that may require different approaches compared to traditional applications of HIA. This research focuses on the development of health consequence scales suited to assessing and comparing health effects associated with climate change and applied within a HIA framework. This assists in setting priorities for adaptation plans to minimize the public health impacts of climate change. The scales presented in this paper were initially developed for a HIA of climate change in Perth in 2050, but they can be applied across spatial and temporal scales. The design is based on a health effects pyramid with health measures expressed in orders of magnitude and linked to baseline population and health data. The health consequence measures are combined with a measure of likelihood to determine the level of risk associated with each health potential health impact. In addition, a simple visual framework that can be used to collate, compare and communicate the level of health risks associated with climate change has been developed.